Evaluating the Impact of Vernacular Façade Design on Indoor Thermal Performance in Malaysia’s Modern Masjids - Mohd Nawayai, Siti Salwana; Denan, Zuraini; Sanusi, Aliyah Nur Zafirah; Mohd Nawawi, Norwina (International Journal of Environment, Architecture, and Societies, 2023)
Accessing buildings for evaluation on architectural concerns are raised as some designers create the call to revive indigenous architecture when a trend of adopting foreign or international architectural style is widely spreading. The quests for cultural identity in Malaysia towards sustainable contemporary buildings require research of past achievements. Vernacular masjid is known to adhere to principles of passive design as the key to thermal comfort. Researchers posed questions on the extent of flexibility in vernacular architectural concepts, concerning design adaptation on modern masjids for optimal thermal performance. This experimental research aimed to evaluate the outcome of modern masjid façades designed with the vernacular concept in Malaysia. In the literature, research brings together variables such as building height, façade shading, serambi openings, as well as materials and construction details. A quantitative analysis led this investigation through observation and field survey on stratified random samples of modern vernacular masjids in Malaysia. Air temperature and relative humidity were recorded using a MIC-98583 sensor with ±0.6 °C accuracy in temperature and ± 3 % accuracy in relative humidity. Wind speed was measured using an AVM-305 sensor with ± 0.2 m/s accuracy. The empirical finding highlights serambi opening-to-wall design as the most significant element of vernacular architecture found in building façade that influences indoor thermal performance in modern vernacular masjids. The result could become an extremely useful guideline for designers to create the sustainable design in the future.